A Genetic Variation in the Neonatal Fc‐Receptor Affects Anti‐TNF Drug Concentrations in Inflammatory Bowel Disease. (October 2016) - Billiet, Thomas; Dreesen, Erwin; Cleynen, Isabelle; Wollants, Willem‐Jan; Ferrante, Marc; Van Assche, Gert; Gils, Ann; Vermeire, Severine
Abstract : OBJECTIVES: Ample evidence exists that Anti‐tumor necrosis factor (TNF) concentrations during induction determine short and long‐term outcome in inflammatory bowel disease (IBD). We investigated if a variable number of tandem repeats (VNTR) polymorphism in the neonatal Fc‐receptor (FcRn), responsible for extending half‐life of IgG, influences anti‐TNF concentrations in patients with IBD. METHODS: Retrospective single‐center study, including a cohort of 395 infliximab (IFX) naive IBD patients treated with IFX 5 mg/kg on weeks 0, 2, and 6 and a second cohort of 139 adalimumab naive patients, treated with adalimumab 160‐80‐40 mg on weeks 0, 2, and 4. Area under the serum anti‐TNF concentration‐time curve (AUC), from week 2 and 6 for IFX and week 2 and 4 for adalimumab, was used to identify factors influencing these drug concentrations. RESULTS: The VNTR2/VNTR3 genotype was associated with a 14% lower IFX AUC compared with patients homozygous for VNTR3/VNTR3 ( P =0.03), although this effect became apparent only when immunogenicity (26% lower concentrations, P =9 × 10 −5 ) was not present. Prior anti‐TNF use predicted a 27% lower IFX AUC ( P =0.002). Similarly, VNTR2/VNTR3 patients had a 24% predicted lower adalimumab AUC than VNTR3/VNTR3 patients ( P =0.005). The combined presence of VNTR2/VNTR3 genotype, male gender, and prior IFX use predicted a 41% lower adalimumab AUC concentration ( P =0.04). CONCLUSIONS: The VNTR2/3 genotype in the FcRn gene is associated with lower IFX but also lower adalimumab drug exposure during induction in patients with IBD. Previously identified pharmacokinetic modifying factors were confirmed. Identifying risk factors in patients is important as higher induction doses may be needed to ensure optimal disease outcome.